2012
DOI: 10.1108/20463161211270464
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perspectives on leadership practices and motivation in Islamic private schools, Southern Thailand

Abstract: Purpose -The purpose of this paper is to present teachers' perspectives on leadership practices and motivation in the context of Islamic private schools in Songkhla, a southern province of Thailand. Design/methodology/approach -A survey method was employed to collect data from teachers in six selected Islamic private schools in Songkhla. Findings -The statistical data indicate that teachers' motivation is significantly related to principals' transformational leadership practices, as perceived by teachers. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
1
8
0
1
Order By: Relevance
“…Tajasom and Ahmad (2011) indicated that principals in private schools have greater power and effects on teacher motivation than in public schools when they use transformational rather than transactional leadership. A similar conclusion was drawn in Islamic schools in Thailand, where Othman and Wanlabeh (2012) found that although teachers perceived that their principals exhibited transformational leadership more frequently than transactional leadership, the principals were viewed to display more idealized influence and inspirational motivation rather than individual consideration and intellectual stimulation practices.…”
Section: Literature Overviewsupporting
confidence: 65%
“…Tajasom and Ahmad (2011) indicated that principals in private schools have greater power and effects on teacher motivation than in public schools when they use transformational rather than transactional leadership. A similar conclusion was drawn in Islamic schools in Thailand, where Othman and Wanlabeh (2012) found that although teachers perceived that their principals exhibited transformational leadership more frequently than transactional leadership, the principals were viewed to display more idealized influence and inspirational motivation rather than individual consideration and intellectual stimulation practices.…”
Section: Literature Overviewsupporting
confidence: 65%
“…Students tend to have big challenges to focus on learning. A major challenge for students in urban areas is environmental influences and uncontrolled technological advances [46], [47]. While students in rural areas stated in the interview as:…”
Section: Understanding the Conceptual Of Islamic Education In Madrasa...mentioning
confidence: 99%
“…When combined with appropriate work discipline, teachers with intrinsic and extrinsic motivation will be more successful. Othman and Wanlabeh (2012) conducted research and discovered a link concerning transformational leadership techniques and teacher motivation. Same assessment and evaluation in the research study of Eyal and Roth (2011), which resulted to school administrators' leadership style had a significant impact on teacher motivation.…”
Section: Teacher Work Motivationmentioning
confidence: 99%